(untitled) (Raparin Journal of Humanities (RJH), 2023)
This article examines the dynamics of class formation from a historical sociology perspective after the formation of the Kurdistan Regional Government (KRG), roughly from 1991 to 2021. It then reviews the KRG period (1991-2021) to trace the process of class formation in the newly-born government. After that, the researchers explore the pattern and nature of class structure and the state in the Southern Kurdistan from 1991 to 2021. This article presents the role of the world economy and the Southern Kurdistan political parties in class formation. For example, the government relied on the selling of natural resources such as crude oil, and a small proportion of people received a tremendous amount of wealth from the government by utilizing political power, and their class position changed to a new one, which is a bourgeois class. As this is a historical sociology study, the following theories will be used: Dependency theory and the world-systems theory are essential in this article because they will evaluate the relationship between classes and compare the Southern Kurdistan with other countries in the capitalist world system. The qualitative methods which have been used in this article include critical analysis of written sources and secondary data, including official statistics of the KRG.